The incomprehensibility of God Augustine as a negative theologian. - Van Geest, Paul, 1964- (Leuven Peeters, 2011)
Augustine's way of speaking about God has been frequently deplored. It has been dismissed as too confident regarding the content of its assertions and too narrowly confined. The reception of Augustine's work appears to indicate that there was not a little truth to this view. Augustine's affirmative statements on God's essence and activities constituted the 'initial capital' of Christian theology and spirituality. In contemporary religion, a tendency is in evidence to deny that too specific an image of God can really contain absolute truth. Fully formulated religious truths have to be placed in perspective, or must even be deconstructed, especially if the suspicion arises that they inhibit openness to authentic religious experiences of unity and harmony. Given such an outlook on religion, it seems understandable that those who take contemporary culture's renewed interest in religion seriously ignored Augustine's work as an authoritative source for 'post-Christian' discourse about God.
Affirmative or negative discourse about God? : Augustine's background and context -- Acceptance of unknowing and aversion to anthropomorphisms : De ordine (386) and De Genesi aduersus Manicheos (389) -- Realizing the incomprehensibility of God : De diuersis quaestionibus ad Simplicianum (395) -- Sensory perceptions as a mandatory requirement for the via negativa towards God. Confessiones (397-401) -- Evocation and confrontation : In epistolam Johannis ad Parthos (407) -- Seeing God in the flesh? : Letters to Italica, Paulina and Fortunatianus (408-414) -- The incomprehensibility of God as a cause of concern -- Negation in affirmation : De Trinitate (400-427) -- The emerging of orthodoxy, heterodoxy, and negativity in Augustine's preaching. Sermo 117 : Contra Arianos -- Convinced of predestination and yet uncertain about God? -- Approaching God : an assessment.
Keywords: Augustine, -- Saint, Bishop of Hippo; God (Christianity) -- Knowableness; Negative theology -- Christianity; 276 =71 AUGUSTINUS -- Latijnse patrologie--AUGUSTINUS